Immunohistochemical analysis of pyloric gland adenomas using a series of Mucin 2, Mucin 5AC, Mucin 6, CD10, Ki67 and p53 - Vieth, Michael; Kushima, Ryoji; Mukaisho, Ken Ichi; Sakai, Rie; Kasami, T.; Hattori, Takanori (Virchows Archiv, 2010)
A pyloric gland adenoma (PGA) of the stomach was first described in a book chapter in 1976 by Kurt Elster and has been rarely reported in the literature. We expanded the current immunohistochemical data of these adenomas in a detailed series to further analyse the immunhistochemical status of PGA. From 60 patients with PGA with and without adenocarcinomas of the gastrointestinal tract, an immunhistochemical panel of Mucin 2, Mucin 5AC, Mucin 6, CD10, Ki67 and p53 was used to define the expression of these markers. All PGA were positive for Mucin 6 (deep mucoid glands), which they express over the whole lesion up to the surface. Mucin 5AC expression varies from case to case. A transition from gastric to intestinal differentiation can be observed focally as depicted by Mucin 2 and CD10 in 65% of the cases. The gastric corpus mucosa of elderly patients with either Helicobacter pylori gastritis or autoimmune gastritis is highly affected. Almost 47% of all PGA already underwent malignant transformation into adenocarcinoma. Significant immunohistochemical differences could be detected between PGA with and without adenocarcinoma regarding ki67 and p53. The diagnosis of PGA can be confirmed immunohistochemically by staining against apomucin 6 and apomucin 5AC. Focal intestinal differentiation supports the hypothesis that gastric adenocarcinomas can initially develop from carcinomas of the gastric type and transform into intestinal type later on. The high frequency of malignant transformation of PGA underlines its high potential for invasive malignancy. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Adenocarcinoma; Gastro-intestinal tract; Immunohistochemistry; Pyloric gland adenoma